Contact, moral foundations or knowledge? What predicts attitudes towards women who undergo IVF - Alicja Malina; Marta Roczniewska; Julie Ann Pooley (BMC, 2021)
Abstract Background The willingness to try in vitro fertilization (IVF) as an infertility treatment, as well as its psychosocial consequences for couples, may be influenced by how they perceive the attitudes of general public towards this procedure. The focus of the current study was to identify predictors of attitudes towards mothers who underwent IVF to conceive a child. Three predictors were derived from attitude components: contact with someone who had undergone IVF (behavior), moral foundations (emotions), and the level of knowledge (cognition) about IVF. Method In total, 817 participants (118 male and 692 female, 7 unreported) from Poland took part in the study. Participants were asked whether they knew a person who underwent IVF, completed a Moral Foundation Questionnaire, and answered a pre-piloted IVF knowledge test. Attitudes towards women who utilised IVF were measured with a modified Bogardus Social Distance Scale. Data were analysed using hierarchical and logistic regression analyses. Results The results showed that there was a weak link between previous contact with a person who underwent IVF and a positive attitude toward a woman who underwent IVF. The attitudes was also predicted by moral foundations: positively by care/harm and fairness/cheating foundations, and negatively by sanctity/degradation. Importantly, more knowledge about IVF was linked with a more positive attitude towards IVF, and this effect explained additional variance over and above moral foundations. Conclusions Our study implies the need of psychoeducation to prevent stigmatization of individuals who try IVF due to infertility.